KAJIAN IDENTIFIKASI POTENSI DAN PERMASALAHAN SUMBERDAYA AIR: Studi Kasus : Kabupaten Belitung - ASEP HARIYANTO; K. HERRY ISKANDAR (Jurnal Perencanaan Wilayah dan Kota, 2011)
This study aims to provide an overview of potential and problems of water resources contained in Belitung District, as well as inputs for the Government Belitung Regency in order management and utilization of water resources. The method used is the primary method of survey and secondary survey methods. Primary survey methods include: surveys of ground water, spring surveys, and surveys of surface water. While the method of secondary survey conducted through secondary data collection and is a confirmation of the results of previous studies or Based on the information from the agencies related to water resource management. The method of analysis used in this study is "Mock method". Mock The method is a method for estimating the presence of water based on the concept of water balance. Overall discharge calculations with Method Mock refers to water balance, where the volume of total water on earth is fixed, only the circulation, and distribution varied. Based on the results of the analysis has been done, can know the potential water resources are owned Belitung Regency include: watershed and river discharge that has a large enough reliable; under-mined under the savings used as raw water sources as ponds that use river water reservoir and water rain; and groundwater. In addition to the potential, there are some problems related to water resources management in Belitung District include: water pollution; flooding problems; dryness; as well as deterioration of water quality problems.